Birthday Greeting: Happy birthday to Ilona Ormos, The Former Dean Of The Faculty Of Landscape Architecture And The First Head Of The Department Of Garden Art. - Jámbor, Imre (4D Journal of Landscape Architecture and Garden Art, 2012)
In the life of a woman, age does not hold significant importance, yet there are moments that invite reflection and celebration. This milestone has arrived for Ilona Ormos, whose remarkable contributions to garden art education, landscape architecture history, and monument protection have shaped the field in Hungary.